Dynamic dissolutions and unifications. (2nd February 2017) - Ellis, Christopher J.
Abstract : I reexamine the key results from the literature on the size and number of countries under different political institutions in a simple dynamic model. I find that the canonical static results that democracies lead to too many too‐small countries and that Leviathans lead to too few too‐large countries no longer necessarily hold. The key dynamic element that drives the new results is that public goods are modeled as public capital; this changes the incentives to unify or divide countries. I also show that there are hysteresis effects on the size and number of countries; that is, arbitrary initial configurations of national boundaries may tend to persist because of the initial public capital location decisions they promote.